Uwagi w sprawie odpowiedzialności przewoźnika w nowym prawie przewozowym - Napierała, Jacek (Wydział Prawa i Administracji UAM, 1985)
The aim of the present study is to establish in what way the legislator has distributed the so-called carriage risk between the parties to the contract under the new carriage law. With this purpose in mind, certain issues regarding the liability of the carrier, of a more general character, have been analised, as well as those concerning specific types of rights to which persons using carriage services are entitled. Such a formulation of the problem enables a simultaneous discussion of the liability deriving from an inadequate execution of both, a carriage contract of persons and that of things. One might discuss the distribution of the carriage risk by means of an analysis of the different types of rights to which the contracting parties are entitled, in the event of a lack of exucution or an inadequate execution of carriage services. Among the rights aiming at a proper change in the legal relationship there is noticeable a right to validate performance through the so-called execution by substitution. The contents of this right will in practice be dependent on the interpretation of the concept of "circumstances rendering the execution of a contract, in accordance with its terms, impossible". Unfortunately, the Act does not provide for those rights of travellers, the realization of which would lead to making the payment for services conform to a decreased performance value. In this situation, it seems necessary to enlarge upon the postulate of basing legal sanctions in such cases on general principles. We are concerned here with those stiuations in which the carrier charges an additional payment for a special standard of the services. The party to the carriage contract is also entitled to rights of a nullifying character, as for e.g. the right to renounce a contract. In the new act, there is a regulation guaranteeing a return of undue performance and a return to the precontractural state in those situations, when further travel has hecome pointless for the contracting party. The lack of execution or the inadequate execution of a resolution by the carrier, might be the cause of a damage to the contracting party's property. A distribution of the risk of bearing the negative consequences of such developments weighing upon the parties to the carriage contract, depends on the contents of the specific preconditions of indemnity liability, such as 1) a breach of the contents of the relationship resulting from an obligation linking the parties, 2) the lack of circumstances exempting the carrier from liability, 3) the appearance of damages, 4) the existence of a causal nexus between the lack of execution and the damage, 5) the contents of the indemnity liability of the carrier. The problems of the carrier's indemnity liability, which appear at the reading of the new carriage law have been discussed in the above order.
Remarks on the Liability of the Carrier under the New Carriage Law